Temporal correlations in population trends: Conservation implications from time-series analysis of diverse animal taxa. (December 2015) - Keith, David; Akçakaya, H. Resit; Butchart, Stuart H.M.; Collen, Ben; Dulvy, Nicholas K.; Holmes, Elizabeth E.; Hutchings, Jeffrey A.; Keinath, Doug; Schwartz, Michael K.; Shelton, Andrew O.; Waples, Robin S.
Abstract: Population trends play a large role in species risk assessments and conservation planning, and species are often considered threatened if their recent rate of decline meets certain thresholds, regardless how large the population is. But how reliable an indicator of extinction risk is a single estimate of population trend? Given the integral role this decline-based approach has played in setting conservation priorities, it is surprising that it has undergone little empirical scrutiny. We compile an extensive global dataset of time series of abundance data for over 1300 vertebrate populations to provide the first major test of the predictability of population growth rates in nature. We divided each time series into assessment and response periods and examined the correlation between growth rates in the two time periods. In birds, population declines tended to be followed by further declines, but mammals, salmon, and other bony fishes showed the opposite pattern: past declines were associated with subsequent population increases, and vice versa. Furthermore, in these taxa subsequent growth rates were higher when initial declines were more severe. These patterns agreed with data simulated under a null model for a dynamically stable population experiencing density dependence. However, this type of result could also occur if conservation actions positively affected the population following initial declines—a scenario that our data were too limited to rigorously evaluate. This ambiguity emphasizes the importance of understanding the underlying causes of population trajectories in drawing inferences about rates of decline in abundance. Highlights: We evaluated consistency of abundance trends in over 1300 vertebrate populations. In mammals and fish, declines tended to be followed by increases, and vice versa. This could indicate that declines do not reliably predict risk in these taxa. It could also reflect results of effective conservation actions. Informed management requires an understanding of causes of population trends.